Investigation of Some Real Estate Valuation Problems in Turkey - Varol Koç (Journal of Advanced Research in Natural and Applied Sciences)
The urban population increases after the industrial revolution also increased the commercialization of real estate. In the future, this situation would require being able to determine the real estate values more than before. Today, real estate values are of much greater importance in terms of socioeconomic relations and activities in the world. Establishing a standardized real estate valuation system is among the important duties of public administrations. However, in general, the countries that could not catch up with the industrial revolution in the world and whose industrialization started very late and were not mature enough, could not reach the desired level in terms of real estate valuation. In other words, lagging in industrialization naturally leads to being late and behind in the real estate valuation branch, which is an output of industrialization. The problem created by this situation cannot remain local in today's socioeconomically globalized world. Therefore, the problem affects the whole world and developed countries. In this context, as an example, this study presents the contradictions related to the real estate legislation in Turkey and the application errors in valuation and offers suggestions for the elimination of all these.